Effect of Tasks Complexity and Visualization on Investment Decision-Making - Luciana Spica Almilia; Monica Dira Anas Hartika (Magister Akuntansi Universitas Pancasila, 2022)
ABSTRACT This study examines the differences in investment decision-making, as measured by the accuracy, confidence, and calibration levels of investment decisions between participants who receive tasks with different levels of complexity and information visualization. It involved a laboratory experiment among accounting students who had taken or were taking courses in Financial Statement Analysis and Investment and Capital Market Management. The final sample comprised 172 participants who passed the manipulation check and the general accounting knowledge test. A 2 × 2 (within subject) experimental design was used for the analysis: task complexity (high and low) and information visualization (high and low). The results indicate that for nonprofessional investors, the complexity of the task has the most effect on investment decision-making compared to information visualization. Nonprofessional investors obtain information with high visualization, tasks with high complexity can reduce the level of accuracy, trust, and calibration in their decision-making. This is because a nonprofessional investor is more focused on the difficulty of the assignments that must be resolved, and thus, even a high level of information visualization does not help in investment decision-making.